EFEKTIVITAS MODEL TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA KARTU BENAM DALAM MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS III SDN 1 GETAS PEJATEN - Aprillia, Putri; Ratnasari, Yuni; Fakhriyah, Fina (STKIP Persada Khatulistiwa Sintang, 2026)
This study was motivated by the lack of variation in the learning process, including the limited use of instructional models and media. As a result, students perceived learning as less enjoyable, which contributed to their low interest in the Integrated Science and Social Studies (IPAS) subject. The purpose of this study was to examine the effectiveness of the Teams Games Tournament (TGT) learning model assisted by “kartu benam” media in improving students’ learning interest. This research employed a quantitative pre-experimental design using a one-group pretest–posttest design. The population and sample consisted of 39 third-grade students at SDN 1 Getas Pejaten. Data were collected through observation, interviews, written tests, questionnaires, and documentation. Data analysis techniques included the paired samples t-test and N-Gain test. The results of the paired samples t-test showed a significance value of 0.000 < 0.05, indicating a significant effect. The N-Gain score was 0.65, categorized as a “high” improvement, while the N-Gain percentage was 65.72%, classified as “moderately effective.” In conclusion, the TGT learning model supported by kartu benam media is effective in improving students’ interest in learning IPAS.